Brand Image Dan Product Performance Terhadap Customer Loyalty: Customer Satisfaction Sebagai Mediasi - Eric Cantona; Hetty Karunia Karunia Tunjungsari (Jurnal Manajerial Dan Kewirausahaan, 2019)
The purpose of this research is to examine whether 1) brand image can give significant and positive impact on customer satisfaction 2) product performance can give significant and positive impact on customer satisfaction 3) brand image can give significant and positive impact on customer loyalty 4) customer satisfaction can give significant and positive impact on customer loyalty 5) customer satisfaction mediates the impact of brand image on customer loyalty. Sample was selected using convenience sampling method amounted to 100 respondents. Data processing techniques using structural equation modeling with SPPS 24.00 program. The result of this study shows that product performance have significant impact to customer satisfaction, but brand image doesn’t, brand image and customer satisfaction has significant impact to customer loyalty, and customer satisfaction mediates the impact of brand image on customer loyaltyTujuan penelitian ini adalah untuk menguji apakah 1) brand image dapat memberikan pengaruh yang signifikan dan positif terhadap customer satisfaction 2) product performance dapat memberikan pengaruh yang signifikan dan positif terhadap customer satisfaction 3) brand image dapat memberikan pengaruh yang signifikan dan positif terhadap customer loyalty 4) customer satisfaction dapat memberikan pengaruh yang signifikan dan positif pada customer loyalty 5) customer satisfaction dapat memediasi pengaruh brand image pada loyalitas pelanggan. Sampel dipilih menggunakan metode convenience sampling sebanyak 100 responden. Teknik pengolahan data menggunakan pemodelan persamaan struktural dengan program SPPS 24.00. Hasil dari penelitian ini menunjukkan bahwa product performance memiliki dampak yang signifikan terhadap customer satisfaction, tetapi brand image tidak, brand image dan customer satisfaction memiliki dampak yang signifikan terhadap customer loyalty, dan customer satisfacion memediasi pengaruh brand image pada customer loyalty.